PENGARUH KEGIATAN HPHTI TERHADAP KARAKTERISTIK POLA ALIRAN - , Witarya, S. Hut ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The land cover in forest areas in Jambi Province has experienced changes, with its changing pattern into non-forestry purposes, particularly in the logged over lands resulted from the forest concessionsâ activities (HPH) which are distributed nearly in every conservation zone, ranging from the upstream (the buffer zone of Kerinci Seblat National Park) to downstream watersheds (DAS) of Batanghari (Peatland Protected Areas, the Buffer Zone of Berbak National Park). The non-based preservation of forest area management in a watershed will alter the balance of water system in the watershed, including rain, runoff, river flow, absorption, ground water flow and evapotranspiration and other elements. One of the indicators of a watershedâs conditions which is deemed impaired is when the coefficient value of the flow tends to continuously increasing from year to year. Significant damage to forests will change the riverâs characteristic, which originally flows throughout the year (perennial) into a dry river during the dry season (intermitern). In general, the procedure performed in research activities was initiated by conducting observations and field investigation, literature review and secondary data collection, field observations, analysis of secondary data and field observations, formulating conclusions, and the last was the preparation of paper. The research method used was by means of manual calculation of excel program. Based on the calculation conducted from the period of the year 2000 to 2006, the value of KRS obtained ranges from 6-25, thus Tapah sub-watershed area is included in a good category, i.e. KRS value of < 50. The condition of Tapahâs discharge does not change significantly with the logging pattern implemented by the company. Judging on this condition, it indicates that the condition of Tapah subwatershed area does not experiences significant changes in the flowâs hydrograph characteristics due to HPHTI activities